The Pathophysiology of Septic Shock - RUMPA SAHA,; S. DAS,; R. CHATTERJEE,; I. KAUR, (International Journal of Pharma and Bio Sciences, 2010)
While writing this review, Microbiologists, in collaboration with Anaesthetists and Intensivists, have kept in mind the incidence of sepsis and septic shock along with its mortality and morbidity. Moreover, recent advances have been made in the in understanding of the pathophysiology of sepsis and the genesis of septic shock. This has led to the development of new approaches to treatment. Hence early identification and aggressive management will finally lead to reduction of overall mortality. Thus we have tried to highlight the evolving concepts underlying the pathogenesis of septic shock for better understanding and appropriate management outcomes.